Generalized Difference λ-Sequence Spaces Defined by Ideal Convergence and the Musielak-Orlicz Function - Awad A. Bakery (Abstract and Applied Analysis)
We introduced the ideal convergence of generalized difference sequence spaces combining an infinite matrix of complex numbers with respect to λ-sequences and the Musielak-Orlicz function over n-normed spaces. We also studied some topological properties and inclusion relations between these spaces.